The impact of landscape design on house prices and values in residential development in urban areas - Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Zen, Ismawi; Mohd Shahli, FitryNadia (Elsevier, 2014)
Focusing on a world class living environment, a good quality residential area can be highlighted as an important issue in creating a sustainable living environment. However, limited green spaces within the proximity of residential properties are not supporting the landscape space and are not conducive to living space. The aim of the paper is to investigate the impact of landscape design on house prices and values in residential development particularly in urban areas. The paper employed quantitative approaches which include i) a questionnaire survey; and ii) an observation. This empirical study is based on the findings of case studies conducted in several residential areas in Klang Valley. The findings show that the residents have very clear ideas on how much green space is really important in residential areas in order to create a sustainable residential environment. Despite the absence of public actions in terms of providing information, encouraging participations in the survey and promoting awareness of those interviewed have shown considerable interest in promoting landscape design to be applied in residential development. The perceptions of the quality and quantity of landscape designs in residential areas especially in Klang Valley can be further researched for future study.